Lab-on-a-chip technology platform for biophotonic applications - Pezeshki, Hamed (2021)
Discovering the properties of individual biological particles is in its early stages. Parallel advancements in nanotechnology, e.g. fabrication of miniaturised lab-on-a-chip biosensors, and bioengineering, e.g. improved microscopy and spectroscopy techniques, are needed to enable bioscientists to proceed more in these fields. Therefore, there is a high demand for the development of a lab-on-a-chip technology platform that possesses low damage to bioparticles (i.e. lower photon energies), good signal to noise ratio for rapid and reliable measurements, high throughput (e.g. parallel measurements and/or sequential trapping, characterising, de-trapping), and low fixed and operating costs for the system. This thesis aims at the development of a lab-on-a-chip technology platform for biophotonic applications leading into the realisation of high throughput, mass-produced, and miniaturised lab-on-a-chip biosensors. The proposed technology platform offers high throughput by making sequential trapping/characterising/de-trapping and parallel measurements possible at the single molecule level. It can offer improved signal to noise ratio (attractive for Raman and coherent anti-Stokes Raman spectroscopies) and has a miniaturised footprint. It can also cause low damage to bioparticles by using lower photon energies, i.e. longer wavelengths photons, via conducting surface-enhanced coherent anti-Stokes Raman spectroscopy (SECARS) and metal-enhanced two-photon excited fluorescence (ME-TPEF). To achieve this aim, the thesis presents a lab-on-a-chip technology platform which consists of three parts, each of which illustrates specific functionality. The first part includes plasmonic nanostructures for performing nanoplasmonic trapping and interrogation of mesoscopic particles. Through localised surface plasmons, plasmonic nanostructures can confine light in nanoscale hot spots, i.e. nanosized gaps between plasmonic nanostructures, with ultra-high electric field enhancement. The hot spots produce strong near-field gradient forces by which trapping and manipulating mesoscopic particles become possible. The significant field enhancement by the plasmonic nanostructures increases the options for characterising the trapped bioparticle with techniques such as TPEF and CARS. The nanoscale hot spots of plasmonic nanostructures can also manipulate the incident light, e.g. direction of propagation via development of miniaturised vertical couplers. The lab-on-a-chip technology platform requires a photonic waveguide which provides a low-loss optical path for receiving/transferring light from/to plasmonic nanostructures. Coupling plasmonic nanostructures to a low-loss waveguide, which needs to be transparent in the visible and near infrared (NIR) wavelength ranges, will allow the realisation of a waveguide-coupled biosensor as an on-chip trap/sensor device. The lab-on-a-chip technology platform also requires a component to couple light between a light source and the waveguide-coupled biosensor. Thus, this thesis introduces a new type of a unidirectional hybrid plasmonic-photonic vertical coupler enabling efficient coupling of the incident light to the waveguide-coupled biosensor. Due to its nanoscale size, the coupler facilitates the realisation of a miniaturised lab-on-a-chip platform. Despite recent reports on the development of biosensors, there is a need for a cost-effective miniaturised lab-on-a-chip platform capable of trapping and manipulating bioparticles, and creating multiple parallel measurement channels for arrays of biosensors featuring low damage to bioparticles and good signal to noise ratio. So, by introducing a novel type of a lab-on-a-chip technology platform to overcome some of the existing challenges, this thesis contributes to the advances in bio-photonics with empowering the realisation of biosensing platforms featuring compatibility with integrated circuits, possibility of mass-produced plug-and-play biosensor arrays for bioparticles.